An Elderly Lady with Tetany and Brain Calcification - Fatema, Kaniz; Tanbeen, Shriear; Ashek, Md Sahidul Hoque; Ahmed, Khandaker Sabbir; Saha, Debasish Kumar; Sultana, Rozina; Ahsan, ASM Areef (Bangladesh Critical Care Journal, 2024)
We present the case of a 59-year-old Bangladeshi lady who presented in Intensive Care Unit with tetany and altered level of consciousness. Tetany resolved after giving IV calcium injection. Initial laboratory investigations showed hypocalcemia. Non-contrast CT brain showed irregular bilateral symmetrical calcifications in basal ganglia, thalami, cerebellum and corona radiata. Subsequent laboratory test revealed low parathyroid hormone level. So, she was diagnosed as Fahr’s syndrome due to secondary hypoparathyroidism. This is a rare neurological disorder characterized by metabolic, biochemical, neuroradiological and neuropsychiatric abnormalities due to symmetrical and bilateral intracranial calcifications. Bangladesh Crit Care J September 2024; 12 (2): 160-162